Tomato R-gene-mediated resistance against Fusarium wilt originates in roots and extends to shoots via xylem to limit pathogen colonization - Šimkovicová, Margarita; Kramer, Gertjan; Rep, Martijn; Takken, Frank L. W. (Frontiers in Plant Science, 2024)
Vascular wilt disease, caused by the soil-borne fungus Fusarium oxysporum (Fo), poses a threat to many crop species. Four different tomato resistance (R) genes (I-1, I-2, I-3, and I-7) have been identified to confer protection against Fo f.sp. lycopersici (Fol). These I genes are root-expressed and mount an immune response upon perception of the invading fungus. Despite immune activation, Fol is still able to colonize the xylem vessels of resistant tomato lines. Yet, the fungus remains localized in the vessels and does not colonize adjacent tissues or cause disease. The molecular mechanism constraining Fol in the vascular system of the stem remains unclear. We here demonstrate that an I-2-resistant rootstock protects a susceptible scion from Fusarium wilt, notwithstanding fungal colonization of the susceptible scion. Proteomic analyses revealed the presence of fungal effectors in the xylem sap of infected plants, showing that the lack of fungal pathogenicity is not due to its inability to express its virulence genes. To identify mobile root-derived proteins, potentially involved in controlling fungal proliferation, comparative xylem sap proteomics was performed. We identified distinct pathogenesis-related (PR) protein profiles in xylem sap from Fol-inoculated I-1, I-2, I-3, and I-7 resistant lines. Despite structural diversity, all four immune receptors trigger the accumulation of a common set of four PR proteins: PR-5x, PR-P2, and two glucan endo-1,3-β-D-glucosidases. This research provides insights into Fusarium resistance mechanisms and identifies a core set of proteins whose abundance correlates with defense against Fusarium wilt.